Crisis communication in the #safetravelcampaign in the new normal era - Nadya Shaffira; Hana Silvana (Jurnal Kajian Komunikasi, 2022)
The Covid-19 pandemic has a significant impact on the problems that occur in the world of aviation. Because of the situation, the researcher sees another perspective on how the role of product-oriented social media campaigns in the form of services carried out by PT. Angkasa Pura II in changing public trust in the use and service of domestic air transportation. This study aims to determine the effect of the campaign on attitude change. So, there is a gap in the lack of quantitative research that discusses the relationship between product-oriented social media campaigns in changing people’s trust attitudes in the context of crisis and risk communication. The formulation of the problem in this study was to determine the significant relationship between message content and the structure of the #SafeTravelCampaign message on the attitude of trust using domestic air transportation in the new normal era. The approach used in this research is a quantitative descriptive correlation. The results of the study indicate that the campaign content is delivered well in terms of message content and message structure, it will improve the quality of the content which has an impact on changing the attitude of followers. The presence of campaign content have informative, educational, and entertainment value for followers of the @Angkasapura2 Instagram account. Then the presence of a campaign that worked can also be an example for other organizations or companies to increasing public trust in the use and service of services during the midst of the ongoing pandemic crisis.